The The Influence Of Visual Literacy In Improving Reading Comprehension Of Grade 8 Students At SMPN 01 Buay Madang: The Influence Of Visual Literacy In Improving Reading Comprehension Of Grade 8 Students At SMPN 01 Buay Madang - Fikri, Arief Hadziq; Lestari, Lilia Putri; Zulaikah (ENJEL: English Journal of Education and Literature, 2024)
Visual literacy is important in understanding a language text. One of the characteristics that might improve students' comprehension of reading materials is visual literacy, which includes the capacity to comprehend and interpret visual features like pictures, graphs, and diagrams in text. The use of visual literacy media has become an increasingly important topic in education, especially in the context of students' reading comprehension at the junior high school level. This article aims to find out how visual literacy affects 8th grade reading comprehension at SMPN 01 Buay Madang. This research method uses qualitative methods by using a qualitative descriptive approach and data collection tools in the form of observation, and documentation. The results showed that: (1) there is a significant difference between students who use visual literacy media and those who do not; (2) visual literacy media can help students understand texts more easily and quickly because of the visual elements included in the text that explain the information; and (3) students who use visual literacy media have better comprehension skills and are more adept at applying information when compared to students who only use text without any visual elements. This suggests that visual literacy can be an effective strategy to increase comprehension, especially in digital learning contexts where visual aids are more prevalent. This study offers recommendations for a curriculum that focuses more on the use of visual literacy in classroom instruction with the aim of helping students understand the material more thoroughly and raising the standard of instruction in schools.